Mineralogy and geochemistry of gold mineralization at Southern Part of Ulu Sokor Gold Deposit, Kelantan, Malaysia - Ahmad Fauzan Yusoff; Jasmi Hafiz Abdul Aziz; Muhammad Hatta Roselee (Penerbit Universiti Kebangsaan Malaysia, 2022)
The Ulu Sokor gold deposit is classified as orogenic type deposit with evidence from previous studies on the structural, mineralogical, alteration, fluid inclusion, and stable isotope data. This study focuses on the mineralogy and geochemical analysis of representative ore rock samples from southern part of Ulu Sokor gold deposits. The project area is situated at the North of Kelantan state which lies on the Central Belt of Peninsular Malaysia. The main objective of this research is to determine the gold mineralization enrichment pattern relative to other trace elements based on the new data of mineralogy and geochemical analysis. Gold mineralization is primarily hosted in structurally controlled quartz vein which occurs in various degrees of ductile-brittle environment. Based on the field relationships, ore microscopy and geochemical data analysis, there are two main gold mineralization type in the southern part of Ulu Sokor gold deposit, namely (1) Gold associated and as inclusions in bismuthinite based on the mineralogy study, and (2) Refractory gold occurs as lattice bound in pyrite based on the Au/As molar ratio. In terms of mineral exploration and gold prospecting, the significant enrichment in this study area is Bi. However, some other metals can also be considered as a significant value in this area such as Pb, As, Cu and Zn. From the bulk ore chemistry, the geometric mean values of Au and Bi are 1.9 ppm Au (n=23) and 96 ppm Bi (n=22), respectively. The knowledge base for bismuth minerals in Malaysia would provide a significant targeting clue for the gold mineralization.